Mother-infant interaction context matters for verbal and non-verbal parental mentalization: an initial portrait of associations between parental embodied mentalizing, mind-mindedness, and maternal characteristics in a structured and unstructured context - Gagné, Karine; Lemelin, Jean-Pascal; Tarabulsy, George (Frontiers in Psychology, 2023)
Interest in studying the parental embodied mentalizing (PEM), which refers to implicit and non-verbal processes of parental mentalization, is relatively recent. Therefore, little is known about how PEM, in complementarity with the verbal parental mentalization, is associated with maternal characteristics regarding mother-infant interaction contexts. This exploratory study aimed to investigate the associations between the non-verbal and verbal dimensions of parental mentalization – PEM and mind-mindedness respectively – in relation to a wide spectrum of parental characteristics in different interactive mother-infant contexts (toys and no toys). Among a sample of 107 mother-infant dyads at moderate psychosocial risk, mothers’ sociodemographic information (age, education, and income), psychological characteristics (depression and anxiety), cognitions (self-efficacy and perceived maternal impact), and attitudes (overprotection and parental warmth) were assessed via self-report questionnaires when the infant was 4 and 8 months old. The PEM and mind-mindedness were evaluated through observation made during a videorecorded sequence of mother-infant interaction in a context of free play with and without toys at 8 months of age. The results showed distinct associations between PEM and mind-mindedness regarding maternal characteristics: PEM was associated with the mother’s age, education, anxiety and maternal warmth, whereas mind-mindedness was related to cognitions. Both were linked to family income. Regarding mother-infant interaction contexts (toys vs no toys), the results indicate that the capacity to verbally and non-verbally mentalize differs. These findings shed light on distinctive associations between non-verbal and verbal parental mentalization in relation to certain maternal characteristics, and highlight that the mother-infant interaction context may play an important role in the expression of maternal mentalizing capacity.